Exercise for frailty research frontiers: a bibliometric analysis and systematic review - Wenyuan Xu; Xianghu Zhao; Xianghu Zhao; Meiling Zeng; Shengbing Wu; Shengbing Wu; Shengbing Wu; Yikang He; Meiqi Zhou; Meiqi Zhou; Meiqi Zhou (Frontiers in Medicine, 2024)
BackgroundExercise intervention is a method of improving and preventing frailty in old age through physical exercise and physical activity. It has a positive impact on many chronic diseases and health risk factors, in particular cardiovascular disease, metabolic disease, osteoporosis, mental health problems and cancer prevention, and exercise therapies can also fight inflammation, increase muscle strength and flexibility, improve immune function, and enhance overall health. This study was aimed to analyze research hotspots and frontiers in exercise therapies for frailty through bibliometric methods.MethodsIn this study, data of publications from 1st January 2003 to 31st August 2023 were gathered from the Web of Science Core Collection and analyzed the hotspots and frontiers of frailty research in terms of remarkable countries/regions, institutions, cited references, authors, cited journals, burst keywords, and high-frequency keywords using CiteSpace 6.2.R3 software. The PRISMA reporting guidelines were used for this study.ResultsA collection of 7,093 publications was obtained, showing an increasing trend each year. BMC Geriatrics led in publications, while Journals of Gerontology Series A-Biological Sciences and Medical Sciences dominated in citations. The United States led in centrality and publications, with the University of Pittsburgh as the most productive institution. Leocadio R had the highest publication ranking, while Fried Lp ranked first among cited authors. Keywords in the domain of exercise therapies for frailty are “frailty,” “older adult,” “physical activity,” “exercise,” and “mortality,” with “sarcopenia” exhibiting the greatest centrality. The keywords formed 19 clusters, namely “#0 older persons,” “#1 mortality,” “#2 muscle strength,” “#3 bone mineral density,” “#4 muscle mass,” “#5 older adults,” “#6 older people,” “#7 women’s health,” “#8 frail elderly,” “#9 heart failure,” “#10 geriatric assessment,” “#11 comprehensive geriatric assessment,” “#12 outcm,” “#13 alzheimers disease,” “#14 quality of life,” “#15 health care,” “#16 oxidative stress,” “#17 physical activity,” and “#18 protein.”ConclusionThis study presents the latest developments and trends in research on frailty exercise intervention treatments over the past 20 years using CiteSpace visualization software. Through systematic analyses, partners, research hotspots and cutting-edge directions were revealed, providing a guiding basis for future research.